Development of Biophoto Anodes Using Ulvophyceae Macroalgae - Moenne-Munoz, A; Gonzalez-Figueroa, A; Tasca-Gottardo, F; Tasca-Gottardo, F; Zuñiga-Loyola, C; Zuñiga-Loyola, C (Royal Society of Chemistry, 2022)
Three different macroalgae, i.e., U. lactuca, U. linza, and U. compressa, have been studied for biological photovoltaic energy system (BPVE) using edge plane pyrolytic graphite as the supporting working electrode. The studied biophotoanodes were evaluated in terms of direct electron transfer (DET) and mediated electron transfer (MET) processes. Ferrocyanide (FeCN), p-benzoquinone (BQ), and 1,4-naphthoquinone (NQ) were used as a mediator during biophotovoltaic experiments in the presence and absence of applied light. The electrochemical characterization was performed by cyclic voltammetry (CV) and chronoamperometry. The results show that using BQ during the MET process, the electron transfer to the graphite electrode drastically increases during light conditions, where the most promising biophotoanode was in the presence of BQ and U. linza with a current density of 72.1 ± 9.1 μA cm−2, which represents an increase of almost 2000 times over DET results. Similar results were obtained with U. lactuca and U. compressa. The high performance in the presence of BQ for the three macroalgae has been attributed to the favorable penetration of the quinone molecule to the cytoplasmic membrane, allowing the direct exchange of electrons with photosystem II in the thylakoid structure. © 2023 The Royal Society of Chemistry.